2013
DOI: 10.1007/s12263-013-0353-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of genetic variants of ghrelin, leptin and UCP2 with malnutrition inflammation syndrome and survival in end-stage renal disease patients

Abstract: Malnutrition inflammation syndrome (MIS) is common among ESRD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
3
7
0
1
Order By: Relevance
“…In agreement, previously, it has been already reported that leptin levels were elevated in advanced renal disease patients with normal and mild malnutrition, although leptin was found to be lower in severe and moderate category of malnutrition score [19]. In ESRD patients malnutrition and hypoalbuminemia are common and powerful predictors of morbidity and mortality of these patients [20].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In agreement, previously, it has been already reported that leptin levels were elevated in advanced renal disease patients with normal and mild malnutrition, although leptin was found to be lower in severe and moderate category of malnutrition score [19]. In ESRD patients malnutrition and hypoalbuminemia are common and powerful predictors of morbidity and mortality of these patients [20].…”
Section: Discussionsupporting
confidence: 87%
“…In ESRD patients malnutrition and hypoalbuminemia are common and powerful predictors of morbidity and mortality of these patients [20]. The decreased serum levels of leptin in severe category of malnutrition group might be associated with acquired leptin receptor resistance [19]. Reversely, the lower leptin levels may be implicated to the pathways for hypertension and worsen nutritional and metabolic state in dialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Vaia D. Raikou although were lower in severe and moderate category of malnutrition score [11] in agreement with other previous findings [12] . The decreased serum levels of leptin in severe category of malnutrition group might be associated with acquired leptin receptor resistance [11] .…”
Section: Which Is the Role Of Leptin On Patients In The End Stage Of supporting
confidence: 92%
“…The decreased serum levels of leptin in severe category of malnutrition group might be associated with acquired leptin receptor resistance [11] . However, it has been showed that the levels of acyl ghrelin were lowest in the severe group of malnutrition [11] . Ghrelin is an appetite stimulating hormone and transduces signals to hypothalamic regulatory nuclei that control energy homeostasis.…”
Section: Which Is the Role Of Leptin On Patients In The End Stage Of mentioning
confidence: 98%
See 1 more Smart Citation